1986
DOI: 10.1073/pnas.83.10.3391
|View full text |Cite
|
Sign up to set email alerts
|

Yeast RPO41 gene product is required for transcription and maintenance of the mitochondrial genome.

Abstract: A 4-kilobase DNA fragment carried by a recombinant Xgtll bacteriophage appears to contain most of the coding information for the 145-kDa subunit of the Saccharomyces cerevisiae mitochondrial RNA polymerase. The RP041 gene is located on chromosome VI, as determined by hybridization to electrophoretically separated yeast chromosomes. Hybridization and gene disruption/replacement experiments show that the RP041 gene exists in a single copy and that its product is required for transcription and maintenance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
2
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 34 publications
2
63
2
1
Order By: Relevance
“…9A, lanes 1 (32). The products of these nuclear genes are required for mitochondrial gene transcription and maintenance of the intact mitochondrial genome (15,25,40). It has been reported that RP041 transcript levels and the core polymerase activity increase about fivefold in glycerol, and it has been suggested that the increase in mitochondrial transcript abundance described above may be due to this increase in RP041 levels (42,62 (59).…”
Section: Resultsmentioning
confidence: 99%
“…9A, lanes 1 (32). The products of these nuclear genes are required for mitochondrial gene transcription and maintenance of the intact mitochondrial genome (15,25,40). It has been reported that RP041 transcript levels and the core polymerase activity increase about fivefold in glycerol, and it has been suggested that the increase in mitochondrial transcript abundance described above may be due to this increase in RP041 levels (42,62 (59).…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensively studied T7 RNAP can recognize specific promoter sequences, correctly initiate transcription, and catalyze transcript elongation until termination unaided by auxiliary proteins (reviewed in Cheetham and Steitz, 2000). In mitochondria of the budding yeast Saccharomyces cerevisiae (Greenleaf et al, 1986;Masters et al, 1987), mammals (Tiranti et al, 1997;Falkenberg et al, 2002;Gaspari et al, 2004), and other eukaryotic organisms (Cermakian et al, 1996), a nuclear-encoded T7 phage-type RNAP has replaced the ancestral bacterial-type RNAP. Transcription initiation in the mitochondria of yeast and mammals, however, depends on the transcriptional cofactor mtTFB (MTF1, TFBM), which is related to rRNA dimethyladenosine transferases (Winkley et al, 1985;Schinkel et al, 1987;Falkenberg et al, 2002;McCulloch et al, 2002;Matsunaga and Jaehning, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mixture was incubated at 37°C for 1 to 1.5 h at 37°C and passed over a Sephadex G-50 spin column to remove unincorporated rNTPs, and the RNA was precipitated with ethanol. RNA was 3' end labeled in a 20-,ul reaction mixture containing 50 mM N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid (HEPES; pH 7.5), 15 Tn:URA3), whose construction has been described in detail elsewhere (15). Yeast cells were grown to mid-to late logarithmic phase at 30°C in a medium containing 2% Bacto Peptone, 1% yeast extract, and an appropriate carbon source, either 2% glucose (YPD) or 2% galactose (YPGAL).…”
mentioning
confidence: 99%